1994
DOI: 10.1293/tox.7.329
|View full text |Cite
|
Sign up to set email alerts
|

Historical Control Data of Spontaneous Lesions in Beagle Dogs.

Abstract: Abstract:A variety of spontaneous lesions found histologically in control Beagle dogs (males: 91, famales; 97) used in toxicity studies that were conducted at the Biosafety Research Center, Foods, Drugs and Pesticides during a 10 year period, are described.All animals were exsanguinated by incision of the axillary artery under sodium pentobarbital anesthesia at the end of each study. Neoplastic lesions included fibrosarcoma of the heart in a female dog at approximately 27 weeks of age (1.0%) and hemangioendoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In beagle dogs used in toxicity studies, spontaneous ocular lesions are not frequent compared with those in rats and mice. Several histopathological studies on the background reference data described infrequent spontaneous lesions detected in the eyes of beagle dogs used in toxicity studies 39 , 40 , 41 , 42 , 43 , 44 , 45 . The reasons for this seem to be that the breed of dogs used in toxicity studies is limited to the Beagle, the test period is relatively shorter, up to one year, than those in rodents, and the dogs are used at young age in toxicity studies.…”
Section: Spontaneous and Toxic Ocular Lesions In Laboratory Animalsmentioning
confidence: 99%
“…In beagle dogs used in toxicity studies, spontaneous ocular lesions are not frequent compared with those in rats and mice. Several histopathological studies on the background reference data described infrequent spontaneous lesions detected in the eyes of beagle dogs used in toxicity studies 39 , 40 , 41 , 42 , 43 , 44 , 45 . The reasons for this seem to be that the breed of dogs used in toxicity studies is limited to the Beagle, the test period is relatively shorter, up to one year, than those in rodents, and the dogs are used at young age in toxicity studies.…”
Section: Spontaneous and Toxic Ocular Lesions In Laboratory Animalsmentioning
confidence: 99%
“…The majority of the pathology findings noted in the present study were consistent with the common background spontaneous pathology routinely observed in young adult Beagle dogs of this strain (9.5-19 months), as well as with published descriptions of the spontaneous pathology of Beagles. 12,16,18,20,28 Changes in some organs, such as the thymus and bone marrow, could be anticipated given the well-recognized association between the degree of thymic involution and decrease in bone marrow cellularity with increasing age. In the thymus, the histologic pattern of involution was similar to that reported in young adults, 23 with animals >30 months having an increased prevalence of this change.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, publications detailing the incidence of spontaneous pathology findings in Beagles are confined to animals no older than 2 years. 12,[16][17][18]28 While chronic lifetime studies in Beagle dogs have been undertaken at the Lovelace Respiratory Research Institute (LLRI), 19 published data from these studies does not include detailed observations of the spontaneous pathology noted in dogs aged between 2 and 5 years.AstraZeneca had a cohort of older beagle dogs available for use on routine toxicity studies, with the age of all animals exceeding the upper age limit of Beagles routinely used in toxicity testing (>24 months), raising concerns about a lack of suitable age-and strain-matched historical control data and potential impact on the interpretation of histopathology findings.AstraZeneca has a commitment to fully implement the principles of replacement, reduction, and refinement (3 Rs) for the use of animals in research; therefore, the aim of the study described here was to generate a complete ''guideline compliant'' set of hematology, clinical chemistry, and anatomic pathology end points to support the use of these older dogs in preclinical toxicity testing. For the purposes of this article, we define young adult dogs as being aged between 6 and 24 months and older dogs, between 25 and 37 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic remnants of craniopharyngeal ducts were found in 53 percent of dogs of several breeds in one survey 2 . In beagle, the incidence of pituitary cyst is 26.5% (10.5-35.1%) and might not be age-related [4][5][6][7][8] . However, the reports on immunohistochemical studies of the craniopharyngeal duct cysts in dogs have not been published.…”
mentioning
confidence: 99%